2022
DOI: 10.1007/s10854-022-07918-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and electrical characterizations of Cr-doped CuO thin films

Abstract: The polycrystalline copper oxide (CuO) thin films have been produced using method of spin coating onto the soda lime glass (SLG) as well as substrate of p-type Si (1 0 0) wafers at 500 ºC in furnace. The obtained undoped and Cr doped thin films of CuO have been comprehensively characterized via X-ray diffraction (XRD), ultraviolet-vis (UV-vis) spectroscopy, the current-voltage (I-V) and capacitance-voltage (C-V) characteristics for providing information on quality of the crystalline nature, change in energy ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…! o = 18.52 " 3.08E g (7) The dielectric coefficients of thin films were found using the refractive indices calculated by Moss and Herve and Vandemme relations and are given in Table 2.…”
Section: Optical Properties Of Undoped and Ag-doped Cuo Thin Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…! o = 18.52 " 3.08E g (7) The dielectric coefficients of thin films were found using the refractive indices calculated by Moss and Herve and Vandemme relations and are given in Table 2.…”
Section: Optical Properties Of Undoped and Ag-doped Cuo Thin Filmmentioning
confidence: 99%
“…In recent years, copper oxides have been widely used in gas sensors [1], thin film transistors [2], photo-electrochemical cells [3,4], and cross-point memories [5], including electronic and optoelectronic devices due to their energy band gap values differing from 1.5 to 3eV. CuO-based thin films have very prominent advantages due to their relatively high optical absorption properties, non-toxicity, low production costs, and thermal stabilities [6,7].…”
Section: Introduction *mentioning
confidence: 99%
“…For example, band gap values were modified and found to increase as the doping concentration of Cr increased in CuO. 12 In addition, Cr can induce RTFM in CuO. 13 Further, it was observed that Co-doped CuO nanoparticles show superparamagnetism at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In other works, the researchers used Na 14 , Co 15 , Ag, Au, Cr, Pd, Pt, Sb, Si 16 , and Ni 17 as dopants to modify the properties of copper oxides. Furthermore, Cr has been proved to enhance the sensing performance of copper oxides 18 and increase the V OC and I SC of a CuO:Cr/p-Si p–n junction, which is favourable in solar cell applications 19 .…”
Section: Introductionmentioning
confidence: 99%